Penggunaan Bahan Ajar Digital untuk Meningkatkan Keterampilan Membaca Kanji pada Pembelajar Bahasa Jepang Pemula - Nia Septiany; Siti Drivoka Sulistyaningrum; Samsi Setiadi (KIRYOKU, 2026)
This study aims to examine the effectiveness of digital Kanji teaching materials in improving N5-level Kanji reading skills among beginner learners of Japanese. The primary objective is to investigate how the integration of digital learning resources influences students’ ability to recognize and comprehend Kanji characters at the N5 level. The study employed a quasi-experimental design using a pre-test and post-test approach to measure the extent to which the independent variable (digital teaching materials) affected the dependent variable (Kanji reading skills). The findings revealed a significant improvement in students’ N5-level Kanji reading performance after the implementation of digital materials. These results suggest that digital teaching materials not only increase learner engagement but also promote a deeper understanding of Kanji through interactive and multimodal learning features. This research contributes to the field of Japanese language education by emphasizing the pedagogical value of technology integration, which supports the development of more effective and engaging instructional strategies applicable across diverse educational contexts.